2020
DOI: 10.1080/00221686.2020.1744744
|View full text |Cite
|
Sign up to set email alerts
|

Localized roughness effects in non-uniform hydraulic waterways

Abstract: Hydropower tunnels are generally subject to a degree of rock falls. Studies explaining this are scarce and the current industrial standards offer little insight. To simulate tunnel conditions, high Reynolds number flow inside a channel with a rectangular cross-section is investigated using particle image velocimetry and pressure measurements. For validation, the flow is modelled using large-eddy simulation (LES) and a Reynolds-averaged Navier-Stokes (RANS) approach with the k − ε turbulence model. One wall of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
(36 reference statements)
1
1
0
Order By: Relevance
“…Simulations carried out by [30] using a computational grid derived from terrestrial laser scanning (TLS) data of a hydropower-tunnel and a 3D-modelling approach based on the Reynolds-averaged Navier-Stokes (RANS) equations with the k-ε turbulence model showed the possibility to study local pressure variations due to a complex tunnel geometry. A similar conclusion was reported based on the numerical simulations of physical scale model experiments by [29]. However, it should be kept in mind that CFD models require a rigorous verification and validation process.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Simulations carried out by [30] using a computational grid derived from terrestrial laser scanning (TLS) data of a hydropower-tunnel and a 3D-modelling approach based on the Reynolds-averaged Navier-Stokes (RANS) equations with the k-ε turbulence model showed the possibility to study local pressure variations due to a complex tunnel geometry. A similar conclusion was reported based on the numerical simulations of physical scale model experiments by [29]. However, it should be kept in mind that CFD models require a rigorous verification and validation process.…”
Section: Introductionsupporting
confidence: 82%
“…Thus, such scale models are prone to both laboratory and scale effects e.g., [24,26] which may be minimized by further developing existing technologies for scale model production to avoid simplifying assumptions regarding wall roughness characteristics. This becomes possible through the use of computer numerically controlled (CNC) production techniques e.g., [27,28] and a recent study of [29] showed the possibilities to gain further insights into roughness effects in non-uniform hydraulic waterways of hydropower systems using this technique.…”
Section: Introductionmentioning
confidence: 99%